The Pacific Rim as a platform for international investment law harmonization - Mark Feldman; Rodrigo Monardes Vignolo; Cristián Rodríguez Chiffelle (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Over the past decade, active, converging treaty practice in the Pacific Rim region has created substantial momentum for international investment law harmonization. This Perspective argues that such momentum establishes the Pacific Rim region as an exceptionally well-developed platform for achieving further harmonization of the international investment law regime.
Keywords: 330